Band Structure Engineering by Alloying for Photonics - Gong, Chen; Kaplan, Alan; Benson, Zackery A.; Baker, David R.; McClure, Joshua P.; Rocha, Alexandre R. [UNESP]; Leite, Marina S. (Wiley, 2018)
Surface plasmon polaritons (SPPs) enable the deep subwavelength confinement of an electromagnetic field, which can be used in optical devices ranging from sensors to nanoscale lasers. However, the limited number of metals that satisfy the required boundary conditions for SPP propagation in a metal/dielectric interface severely limits its occurrence in the visible range of the electromagnetic spectrum. We introduce the strategy of engineering the band structure of metallic materials by alloying. We experimentally and theoretically establish the control of the dispersion relation in Ag–Au alloys by varying the film chemical composition. Through X-ray photoelectron spectroscopy (XPS) measurements and partial density-of-states calculations we deconvolute the d band contribution of the density-of-states from the valence band spectrum, showing that the shift in energy of the d band follows the surface plasmon resonance change of the alloy. Our density functional theory calculations of the alloys band structure predict the same variation of the threshold of the interband transition, which is in very good agreement with our optical and XPS experiments. By elucidating the correlation between the optical behavior and band structure of alloys, we anticipate the fine control of the optical properties of metallic materials beyond pure metals.
Keywords: band structures; density functional theory; dispersion relations; metal alloys; plasmonics